Hubungan Tingkat Pengetahuan dengan Swamedikasi Penyakit Neurodermatitis pada Pekerja Proyek di PT. Boyang Purbalingga - Anggestia Zakina; Peppy Octaviani; Rani Prabandari (Universitas Borneo Lestari, 2023)
Neurodermatitis or lichen simplex chronicus is defined as a common form of chronic neurodermatitis that presents as dry, patchy areas of skin that are scaly and thick. Self-medication is a person's effort to help himself in the form of self-medicating. This study aims to determine the relationship between knowledge level and self-medication of neurodermatitis in project workers at PT. Boyang Purbalingga. This study used a cross sectional time approach. Research based on SPSS with spearman-rank test of neurodermatitis knowledge level on project workers of PT. Boyang Purbalingga found that most of the respondents had sufficient knowledge level as many as 24 respondents (21.8%) and good knowledge as many as 86 respondents (78.2%). Based on SPSS with spearman-rank test, the level of self-medication of neurodermatitis in project workers of PT. Boyang Purbalingga as many as 7 respondents (6.4%) have sufficient knowledge and 103 respondents (93.6%) have good knowledge. The results of the analysis based on the spearman-rank test obtained a p-value of 0.167 with a significance degree of 5% (0.05). It can be concluded that statistically there is a relationship between the level of knowledge and self-medication of neurodermatitis disease in project workers at PT. Boyang Purbalingga.